Alternative Splicing of In‐Frame Exon Associated with Premature Termination Codons: Implications for Readthrough Therapies. Issue 2 (8th November 2012) - Hinzpeter, Alexandre; Aissat, Abdel; de Becdelièvre, Alix; Bieth, Eric; Sondo, Elvira; Martin, Natacha; Costes, Bruno; Costa, Catherine; Goossens, Michel; Galietta, Luis J.V.; Girodon, Emmanuelle; Fanen, Pascale
ABSTRACT The correction of premature termination codons (PTCs) by agents that promote readthrough represents a promising emerging tool for the treatment of many genetic diseases. The efficiency of the treatment, however, varies depending on the stop codon itself and the amount of correctible transcripts related to the efficiency of nonsense‐mediated decay. In the current study, a screen by in vitro minigene assay of all six PTCs described in exon 15 of the CFTR gene demonstrated alternative splicing to differing degrees for five of them. Of the five, PTC mutations c.2537G>A (p.Trp846*UAG) and c.2551C>T (p.Arg851*) cause the greatest proportion of transcripts lacking exon 15; both mutations altering exonic splicing regulatory elements. In order to increase the amount of full‐length transcripts, different pharmacological treatments were performed showing both negative and positive effects on exon inclusion for the same mutation. Therefore, the total amount of transcripts together with the splicing profile should be assessed to anticipate and improve efficacy of readthrough therapy.